2021
DOI: 10.1186/s12959-021-00291-w
|View full text |Cite
|
Sign up to set email alerts
|

Platelet adhesion in type 2 diabetes: impact of plasma albumin and mean platelet volume

Abstract: Background Altered mean platelet volume (MPV) and plasma albumin has been reported in type 2 diabetes (T2D). MPV is suggested to predict cardiovascular risk but there is a lack of evidence for associations between MPV and platelet adhesion. Plasma albumin and magnesium are other factors reported to influence thrombotic risk. The objectives of this study were to assess the association between platelet adhesion and plasma factors with a potential role to affect platelet activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(66 reference statements)
0
7
1
Order By: Relevance
“…In a study on systemic lupus erythematosus, both cross-sectional and longitudinal studies found no correlation between disease activity and MPV (43). These contradictory results may be because MPV changes are affected by many factors, such as age, gender, diabetes, obesity, and hypertension (44,45). Our study found that there is a difference in MPV between AAV patients and healthy controls, but MPV is not associated with the BVAS disease activity score.…”
Section: Discussioncontrasting
confidence: 73%
“…In a study on systemic lupus erythematosus, both cross-sectional and longitudinal studies found no correlation between disease activity and MPV (43). These contradictory results may be because MPV changes are affected by many factors, such as age, gender, diabetes, obesity, and hypertension (44,45). Our study found that there is a difference in MPV between AAV patients and healthy controls, but MPV is not associated with the BVAS disease activity score.…”
Section: Discussioncontrasting
confidence: 73%
“…A number of papers have shown that plasma HSA can influence platelet activity [21,23,[39][40][41]. More recently, it has been shown that HSA is subjected to different oxidative modifications that can affect its properties.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our study, whereas the majority of samples experienced a decrease in platelet levels. Adhesion and activation of platelets can be prevented or suppressed by protecting the vascular end hotel from being damaged, one of which is by administering of albumin preparations [14], [16], [20], [22], [26].…”
Section: Discussionmentioning
confidence: 99%
“…The function of the glycocalyx in maintaining blood coagulation is characterized by increased levels of plasminogen activator inhibitor-1 (PAI-1). The role of albumin in preventing the elevation of PAI-1 is through stabilization of the endothelial glycocalyx layer [4], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation